Architectural heritage of the Chinese Eastern Railway Station in Boketu - Glatolenkova, Ekaterina; Bazilevich, Michail (project baikal, 2025)
The article is devoted to the study of historical development and the experience of using cultural heritage sites in China related to the construction of the Chinese Eastern Railway (CER) at the turn of the 19th and 20th centuries. The article examines the historical development of the city of Boketu known among Russian emigrants as Buhedu Station. The article presents previously unpublished archival drawings of the station plans and analyzes the modern use of historical buildings and their significance in light of the development of urban environment.